2015
DOI: 10.1523/jneurosci.0652-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Forming Optic Glomeruli Compute Figure–Ground Discriminations inDrosophila

Abstract: Many animals rely on visual figure-ground discrimination to aid in navigation, and to draw attention to salient features like conspecifics or predators. Even figures that are similar in pattern and luminance to the visual surroundings can be distinguished by the optical disparity generated by their relative motion against the ground, and yet the neural mechanisms underlying these visual discriminations are not well understood. We show in flies that a diverse array of figure-ground stimuli containing a motion-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 71 publications
2
63
0
Order By: Relevance
“…from leading to trailing edge. Instead, we propose that the spatial field for bar motion integration is finite (Figure 2A), activated by the bar leading edge, consistent with prior findings showing that a revolving ‘curtain’ elicits steering responses similar to those generated by a discrete bar [32]. …”
Section: Resultssupporting
confidence: 88%
“…from leading to trailing edge. Instead, we propose that the spatial field for bar motion integration is finite (Figure 2A), activated by the bar leading edge, consistent with prior findings showing that a revolving ‘curtain’ elicits steering responses similar to those generated by a discrete bar [32]. …”
Section: Resultssupporting
confidence: 88%
“…Neurons downstream of LCs that interconnect multiple optic glomeruli in the central brain respond to small objects [17], raising the possibility that select LCs may themselves be tuned to small objects. Optophysiological and electrophysiological methods have demonstrated that several LCs are broadly sensitive to visual features such as edges or bars [18,19], yet no study to date has thoroughly explored LCs with small two-dimensional objects.…”
Section: Resultsmentioning
confidence: 99%
“…Further, their response profile has been shown to shift with changes in object size—a larger object will need to move at greater lateral speed to elicit the same response (Geurten et al, 2007). Although small target motion detectors have yet to be identified in Drosophila , recent work has identified a group of lobula plate neurons that encode the features required for a separate but similar behavior known as figure detection (Aptekar et al, 2015)—identifying a foreground stimulus moving against a distinct background. It is possible that these neurons have an important role in AMD, but as they were not probed with small visual targets, their potential role is still unclear.…”
Section: Discussionmentioning
confidence: 99%